Cerro de Enmedio. Eine bronzezeitliche Höhensiedlung am unteren Andarax (Prov. Almería) - Molina Fajardo, Federico; Sáez, Leovigildo; Aguayo, Pedro; Nájera, Trinidad; Carrión, Francisco (Madrider Mitteilungen, 2021)
Deutsche Zusammenfassung folgt.